Examining Job Satisfaction and its Effect on Employee Productivity of a Textile Industrial Unit - Mahboubeh Mohammadi; Sevda Sheikhi Lisar; Sakine Sabery Siyahmazgy; Mohammad Taghipour (International Journal of Behavioral Sciences, 2024)
Productivity, especially the productivity of human resources, which is one of the necessities of the growth and development of every society and organization; It is not achieved by simply increasing salaries and benefits and amenities. Rather, making people productive depends on creating satisfaction and increasing job satisfaction. The current research is a descriptive-correlation method; The purpose of the research is to investigate the relationship between job satisfaction (Powell-e Specter model) using a 35-question questionnaire and human resource productivity (Achio model) using a 25-question questionnaire; Therefore, a main hypothesis and a secondary hypothesis were designed. The statistical population of employees of the production department of Borujerd textile factory (N = 720) from which a sample of 250 people was selected by simple random. Among the indicators of job satisfaction, promotion with an average of 3.77 is in the highest position and work environment is in the lowest position with an average of 3.16. All components of job satisfaction have a positive and significant relationship with the productivity of human resources; finally, job satisfaction has a correlation coefficient of 574. and p<0.001 shows a positive and significant correlation with the productivity of human resources. There is a positive relationship between job satisfaction and human productivity. Also, there is a positive relationship between all components of job satisfaction (salaries and benefits, rewards, participation, promotion, work environment) with human resource productivity.
Keywords: Achio Model; Borujerd Textile Factory; Job satisfaction; Manpower Productivity; Poval E Specter Model